2017
DOI: 10.1177/2156587217701857
|View full text |Cite
|
Sign up to set email alerts
|

Online Training in Mind-Body Therapies: Different Doses, Long-term Outcomes

Abstract: Background.There is a high rate of burnout among health professionals, driving diverse attempts to promote resilience and well-being to counter this trend. The purpose of this project was to assess the dose-response relationship between the number of hours of online mind-body skills training for health professionals and relevant outcomes a year later.Methods.Among 1438 registrants for online training (including up to 12 hours of training on mind-body practices) between December 2013 and November 2015, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 48 publications
1
43
0
1
Order By: Relevance
“…In the same study, Kemper and Khirallah (2015b) found that resilience scores did not improve significantly upon completing the module, 'Introduction to stress, resilience and the relaxation response'; however, in a later study, Kemper and Rao (2017a) found that scores improved 'modestly but significantly' for the same module. In another study, Kemper et al (2017b) examined the relationship between the number of hours of online mind-body skills training and outcomes one year later. Kemper et al (2017b) found that the more hours of training participants completed, the more frequently participants practiced mind-body skills one year later.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the same study, Kemper and Khirallah (2015b) found that resilience scores did not improve significantly upon completing the module, 'Introduction to stress, resilience and the relaxation response'; however, in a later study, Kemper and Rao (2017a) found that scores improved 'modestly but significantly' for the same module. In another study, Kemper et al (2017b) examined the relationship between the number of hours of online mind-body skills training and outcomes one year later. Kemper et al (2017b) found that the more hours of training participants completed, the more frequently participants practiced mind-body skills one year later.…”
Section: Resultsmentioning
confidence: 99%
“…The most common study design was a cohort study; all cohort studies in this review were uncontrolled. All but one of the cohort studies (Kemper, Rao, Gascon & Mahan, 2017b) used a pre-post design.…”
Section: Includementioning
confidence: 99%
See 3 more Smart Citations